Preparing for the possible impending surge of Crimean Congo Haemorrhagic Fever (CCHF) in Pakistan - Sohail, Hamnah; Khan, Ibrahim; Sohail, Saadia (Journal of the Pakistan Medical Association, 2025)
Madam, We are writing this letter to bring your attention to the recent cases of Crimean Congo Haemorrhagic Fever (CCHF), in Quetta, Balochistan and Karachi, Sindh.1, 2 This rings an alarming bell as the cases have spread to multiple parts/provinces of the country. Congo virus belongs to the Nairovirus genus in the Bunyaviridae family. CCHF is a severe zoonotic viral disease with high mortality rates (WHO: 10%-40%), caused by a tick-borne virus that can be transmitted to humans by the bites of hyalomma marginatum or through contact with infected tissue/blood from cattle. This illness is identified by fever and bleeding, frequently accompanied by vague symptoms. Identified in more than 30 countries, CCHF has an incidence of 10000-15000 cases annually. The number of cases has been steadily rising. The seroprevalence of Congo virus in Pakistan is estimated to be 2.7%, having a higher prevalence in the rural areas due to their higher exposure to cattle.3 The confirmation of recent Congo virus cases, underscores the need for better vigilance and appropriate measures. Pakistan’s environment is the perfect breeding ground for ticks to grow, making CCHF an endemic in Pakistan since its discovery in 1976. CCHF infections experience a biannual increase from March to May and again from July to September, due to fluctuating temperatures during these periods.4 Tick bites and direct contact with infected animals immediately after slaughter are the major causes of the spread of this infection. Hence, Eid-ul-Adha puts livestock workers more at risk of this virus. In the next decade or so, Eid-ul-Adha will fall during the summer, when CCHF is more prevalent, indicating the dire necessity of enacting laws governing the killing of sacrificial animals and appropriate post-holiday protocols.5 At present, there is no widely approved vaccine for this disease. Current management is primarily supportive care. Considering these grave facts, if appropriate measures are not taken, Pakistan will soon fall victim to an impending surge of CCHF. Pakistan’s government lacks the robust healthcare infrastructure that is necessary to curb endemics and epidemics. So, appropriate measures and prompt screening is of vital importance. Since the illness’s early stages are marked by flu-like symptoms, many patients are misdiagnosed. Hence, healthcare professionals should be alerted. Increased efforts towards mass awareness should be made. Closer coordination of health departments and intergovernmental organizations is needed. Routine animal surveillance for tick infestation and use of pesticides should be increased in the coming months. Proper reporting of new cases is highly impertinent to prevent further spread. Research efforts and collaborations with international institutions should be augmented to develop better treatment options.